What's new in obstetric anesthesia? Focus on preeclampsia. Issue 3 (August 2015) - Leffert, L.R.
<x xml:space="preserve">Abstract</x> Highlights Preeclampsia-related morbidity/mortality is high; 60% of deaths may be avoidable. Many updated preeclampsia guidelines now promote faster diagnosis and management. Preeclampsia confers risk of vascular and metabolic disease intra- and postpartum. Severe hypertension is often under-reported and under-treated. For general anesthesia, adjuncts can blunt the hemodynamic response to intubation.